2019
DOI: 10.1016/j.lcsi.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Expanding educational chronotopes with personal digital devices

Abstract: The aim of this study is to investigate the role of personal digital devices for negotiating assignments during collaborative work in school. Using video recordings of the peer-to-peer interactions in two math and Norwegian language projects, an interactional analysis (IA) is used to analyse the meaning making and the role of phones and cameras in social interaction. To enable a better understanding of the spatial and temporal dimensions in the school context, the students' interactions with the digital device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Today, digital devices have changed the media ecology of the classroom (Ito et al, 2008) with digital technology reconfiguring the spatial and temporal dimensions of education. Moreover, ubiquitous and continuous connectivity changes the classroom both as a space for learning and a space where social life takes place (Erixon, 2016;Gilje, 2019). This connectivity also makes it possible for young people to expand and develop friendships and interests in participation patterns that Ito et al (2008) describe as "hanging out" (p. 13), "messing around" (p. 20), or "geeking out" (p. 28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, digital devices have changed the media ecology of the classroom (Ito et al, 2008) with digital technology reconfiguring the spatial and temporal dimensions of education. Moreover, ubiquitous and continuous connectivity changes the classroom both as a space for learning and a space where social life takes place (Erixon, 2016;Gilje, 2019). This connectivity also makes it possible for young people to expand and develop friendships and interests in participation patterns that Ito et al (2008) describe as "hanging out" (p. 13), "messing around" (p. 20), or "geeking out" (p. 28).…”
Section: Introductionmentioning
confidence: 99%
“…This connectivity also makes it possible for young people to expand and develop friendships and interests in participation patterns that Ito et al (2008) describe as "hanging out" (p. 13), "messing around" (p. 20), or "geeking out" (p. 28). Further, the smartphone can function as a boundary object, expanding the context of schooling for students (Gilje, 2019). Thus, sociality in classrooms is now grounded in both networked and face-to-face interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The research studies about intersubjectivity in computer-supported activity confirmed the focus on dialogue and added new features (Bober & Dennen, 2001). In particular, the space-time dimension is perceived in an original way (Gilje, 2019;Pifarré & Staarman, 2011;Ritella, Rajala, & Renshaw, 2020;Wegerif, 2001). This perception is not confined to the digital environment but it also changes the way face-to-face space-time is perceived.…”
Section: Defining Intersubjectivitymentioning
confidence: 80%
“…Le chronotope est défini en termes de configurations spatiotemporelles socialement émergentes, où l'espace et le temps sont considérés comme des constructions sociales interdépendantes . Ce concept permet aux chercheurs d'étudier comment les relations spatiotemporelles virtuelles-sociales-matérielles pourraient fonctionner comme un terrain d'apprentissage dans plusieurs contextes (par exemple, Brown et Renshaw, 2006 ;Gilje, 2019). Cependant, de nombreuses études adoptant le chronotope sont de nature exploratoire et doivent être développées à la fois au niveau théorique et méthodologique (voir Ritella et al, 2021).…”
Section: Cadre Théoriqueunclassified